Sex-Determining Region Y Controls the Effects of Fetal Alcohol Exposure on Proopiomelanocortin Gene Expression - Gangisetty, Omkaram; Mead, Edward A.; Sarkar, Dipak K. (Frontiers in Neuroscience, 2021)
Fetal alcohol exposure causes various neurodevelopmental deficits in offspring, including reduced expression of the stress regulatory proopiomelanocortin (Pomc) gene and an elevated stress response for multiple generations via the male germline. Male germline-specific effects of fetal alcohol exposure on the Pomc gene raises the question if the sex-determining region Y (SRY) may have a role in regulating Pomc gene expression. Using a transgenerational model of fetal alcohol exposure in Fischer 344 rats, we determined the role of SRY in the regulation of the Pomc gene. Fetal alcohol exposures, like on the Pomc gene, inhibited Sry gene expression in sperm and the mediobasal hypothalamus in male adult offspring. Fetal alcohol-induced inhibition of Sry gene expression was associated with increased Sry promoter DNA methylation. Additionally, fetal alcohol effects on the Sry gene persisted for three generations in the male germline but not in the female germline. Sry gene knockdown reduced the Pomc gene expression. Sry recruitment onto the Pomc promoter was found to be reduced in the hypothalamus of fetal alcohol-exposed rats compared to control rats. Pomc promoter luciferase activity was increased following Sry overexpression. A site-directed mutagenesis study revealed that SRY binding sites are required for POMC promoter transcription activity. Overall, these findings suggest that SRY plays a stimulatory role in the regulation of Pomc gene expression and may potentially contribute to the fetal alcohol-induced changes in the level of Pomc gene expression for multiple generations.